2015
DOI: 10.1159/000381532
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholinesterase Activity in Alzheimer's Disease

Abstract: Cholinesterase inhibitors (ChEIs) are not allowed to be prescribed in combination, which means that we need to select 1 of 3 ChEIs for use in a patient with Alzheimer's disease (AD). However, there is no quantitative analysis on the differences between these agents. In this article, we propose that plasma cholinesterase activity (pChE) could be used as the standard for differentiating between rivastigmine (Riv) and donepezil (Don) in the management of AD. To date, we have treated 6 patients with Riv 18 mg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It has been observed that there are some pathogenetic factors shared by T2DM and AD (Table 2) such as: chronic inflammation [78][79][80], oxidative stress [79,81], adiponectin deficiency [82], different expression of plasma cholinesterase activity [81,83] and vascular damage [78], as described in detail below. 1) Several studies show that in chronic inflammation process, inflammatory cells, such monocytes and macrophages, produce interleukins, including IL-6 and cytokines, including TNF-.…”
Section: Physiopathological Features Common To T2dm and Admentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that there are some pathogenetic factors shared by T2DM and AD (Table 2) such as: chronic inflammation [78][79][80], oxidative stress [79,81], adiponectin deficiency [82], different expression of plasma cholinesterase activity [81,83] and vascular damage [78], as described in detail below. 1) Several studies show that in chronic inflammation process, inflammatory cells, such monocytes and macrophages, produce interleukins, including IL-6 and cytokines, including TNF-.…”
Section: Physiopathological Features Common To T2dm and Admentioning
confidence: 99%
“…In this case, when we talk about pChE, we refer to BuChE. AD and T2DM are positively related to pChE [83,[103][104][105]. PChE is also positively correlated to SP deposition [105,106] and it is also concentrated in cerebral regions involved in AD [106].…”
Section: ) Another Important Component In Inflammatory Process Is Rementioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that diabetes and AD share some pathogenetic factors, including chronic inflammation [ 3 , 4 , 5 ], oxidative stress [ 5 , 6 ], adiponectin deficiency [ 7 ], abnormal expression of plasma cholinesterase [ 8 ]. Many studies demonstrated the increased risk of AD in diabetic patients and proposed a link between abnormal insulin signaling and the amyloid cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic system, which plays an important role in the regulation of learning, cognition, and memory processes 12 , has been extensively studied for the design of anti-Alzheimer’s drugs 13 , 14 . Currently, three of the drugs approved for AD treatment target on cholinesterase, including donepezil, rivastigmine, and galantamine.…”
Section: Introductionmentioning
confidence: 99%